2017
DOI: 10.1111/jvh.12822
|View full text |Cite
|
Sign up to set email alerts
|

Elastogram quality assessment score in vibration‐controlled transient elastography: Diagnostic performance compared to digital morphometric analysis of liver biopsy in chronic hepatitis C

Abstract: Vibration-controlled transient elastography (VCTE) is widely used for noninvasive fibrosis staging in chronic hepatitis C. However, internal validation is based solely on variability and success rate and lacks reproducible quality indicators. We analysed the graphic representation of shear wave propagation in comparison with morphometric results of liver biopsy, eliminating observer variability bias. Individual elastograms were classified according to two morphologic criteria: extension of wave propagation (le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Regarding fibrosis, collagen proportionate area has been deeply analysed in chronic viral hepatitis 7,16‐22 . Different indications for liver biopsy and peculiarities of NAFLD fibrosis with a predominant centrilobular but not portal pattern, as well as a slower rate of progression compared to chronic hepatitis C, may justify why our samples have higher F0 values (5.4% in our cohort vs 2.7% on average for viral hepatitis cohorts) and lower F4 measurements (13.2% in our cohort vs 20.7% on average for viral hepatitis cohorts) 16‐20,22,38 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Regarding fibrosis, collagen proportionate area has been deeply analysed in chronic viral hepatitis 7,16‐22 . Different indications for liver biopsy and peculiarities of NAFLD fibrosis with a predominant centrilobular but not portal pattern, as well as a slower rate of progression compared to chronic hepatitis C, may justify why our samples have higher F0 values (5.4% in our cohort vs 2.7% on average for viral hepatitis cohorts) and lower F4 measurements (13.2% in our cohort vs 20.7% on average for viral hepatitis cohorts) 16‐20,22,38 .…”
Section: Discussionmentioning
confidence: 81%
“…Digital pathology is based on scanning stained tissue slides into digital images, allowing quantitative analysis 15 . Previous studies used digital analysis for the quantification of collagen fibres and its correlation with fibrosis grade, mainly in chronic viral hepatitis patients 7,16‐22 . Regarding NAFLD, conflicting results have been published for collagen evaluation 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…An additional parameter to consider for maintaining a high quality of the examination is the elastogram pattern that appears on the screen for each measurement. Three categories have been described based on the length of the graphic representation and shear wave dispersal (level of parallelism displayed in the elastogram) [21]. A comparison with biopsy data showed that the diagnostic accuracy of TE was significantly greater if based on the quality of each individual measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Liver fibrosis assessed by vibration-controlled transient elastography correlated with that of liver biopsies for all classes and levels of fibrosis, but this noninvasive modality to estimate liver fibrosis is influenced by the accuracy of individual measurements [15] and the examiner's experience [1]. In addition, the elastography technique has other limits, too, as ultrasound cannot propagate through any environment: recent meal examination, patient obesity, cholestasis or congestion of the liver veins, necroinflammation, presence of ascites [1].…”
Section: Attempts To Assess Liver Fibrosis By Imaging Meansmentioning
confidence: 99%